2021
DOI: 10.1016/j.bbih.2021.100347
|View full text |Cite
|
Sign up to set email alerts
|

Post-acute sequelae of COVID-19: Evidence of mood & cognitive impairment

Abstract: Acute health consequences associated with coronavirus disease 2019 (COVID-19) infection have been thoroughly characterized; however, long-term impacts are not yet understood. Post-acute sequelae of COVID-19 (PASC), also known as Long COVID syndrome, is the persistence of COVID-19 symptoms long after viral infection. In addition to physical symptoms, those with PASC experience changes in mental health, but few studies have empirically examined these effects. The current study investigated mood and cognitive fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
94
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(102 citation statements)
references
References 60 publications
5
94
1
2
Order By: Relevance
“…4 7 9 19 A few studies have explored correlations between subjective cognitive dysfunction and neuropsychological testing deficits with mixed findings. [20][21][22] In this paper, we use patients' own descriptions of their symptoms (using their term 'brain fog') and, when appropriate, the US National Cancer Institute definition of 'neurocognitive symptoms' to describe subjective problems 'to do with the ability to think and reason, [including] the ability to concentrate, remember things, process information, learn, speak, and understand'. 23 Possible proposed biological factors include direct neuroinvasion, 24 viral persistence and chronic inflammation, 25 neuronal injury or toxicity and glial activation, 24 26 microvascular injury, 27 activation of autoimmune mechanisms 28 and Lewy body production, 29 while imaging demonstrates loss of grey matter in patients with COVID-19 in key brain regions.…”
Section: Strengths and Limitations Of Studymentioning
confidence: 99%
“…4 7 9 19 A few studies have explored correlations between subjective cognitive dysfunction and neuropsychological testing deficits with mixed findings. [20][21][22] In this paper, we use patients' own descriptions of their symptoms (using their term 'brain fog') and, when appropriate, the US National Cancer Institute definition of 'neurocognitive symptoms' to describe subjective problems 'to do with the ability to think and reason, [including] the ability to concentrate, remember things, process information, learn, speak, and understand'. 23 Possible proposed biological factors include direct neuroinvasion, 24 viral persistence and chronic inflammation, 25 neuronal injury or toxicity and glial activation, 24 26 microvascular injury, 27 activation of autoimmune mechanisms 28 and Lewy body production, 29 while imaging demonstrates loss of grey matter in patients with COVID-19 in key brain regions.…”
Section: Strengths and Limitations Of Studymentioning
confidence: 99%
“…Research estimates that that 20-30% of acute COVID-19 patients experience lasting psychiatric issues 2,16 although the wider literature on this topic reports a much broader range. Several psychiatric conditions have been reported in Long COVID populations including depression, anxiety, post-traumatic stress, fatigue, cognitive impairment, and sleep disturbance [16][17][18] . There is also inconsistency in the literature regarding typical symptom duration.…”
Section: Introductionmentioning
confidence: 99%
“…There is also inconsistency in the literature regarding typical symptom duration. Studies have indicated that psychiatric symptoms can last weeks to several months, and even up to a year and possibly beyond among severe acute COVID-19 patients 17,19 . It has also been said that persistent psychiatric sequelae gradually subside with the passing of time and so are unlikely to continue indefinitely 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Whether this is directly related to the effects of the virus, effects of physical symptoms of long COVID or effects of the pandemic in general is not completely clear. However, recent studies in both adults and children suggest that mood and cognitive functioning after SARS-CoV-2 infection are impaired when compared to controls with similar pandemic-related experiences [ 31 , 32 ]. Changes in taste and smell including anosmia, ageusia, parosmia, and dysgeusia are reported with acute SARS-CoV-2 infection in children [ 20 ] and adults [ 33 ].…”
Section: Long Covid Symptomsmentioning
confidence: 99%